Alcohol Use and Its Relation with Demographic, Environmental, and Psychological Factors among Adolescents in Nabawan, Sabah - Selly Jaimon; Pravina Deligannu; Fredie Robinson (The Korean Academy of Family Medicine, 2024)
Background: Adolescence is an essential stage of a child’s development, transitioning them into adulthood. During this time, they are vulnerable to various social issues, such as experimenting with alcohol, among others. Although alcohol consumption was proven to be detrimental to physical and cognitive development toward adulthood, and almost one in 10 Malaysian adolescents aged 13 years and above are current drinkers, studies concerning the driving factors are still scarce. This cross-sectional study aimed to determine alcohol use among 244 adolescents in Nabawan, Sabah. Methods: This study assessed the associations between alcohol use and three potential factors: demographic, environmental, and psychological. Respondents who were selected through stratified proportionate random sampling answered a set of assessment tools. Results: Results showed that 30.7% (95% confidence interval [CI], 24.91–36.48) of Nabawan adolescents use alcohol. Analysis revealed that older age adolescents 18 years and 19 years, respectively (adjusted odds ratio [aOR], 3.93; P=0.021; aOR, 5.38; P=0.003), having parents (aOR, 4.11; P=0.001) and peers (aOR, 11.57; P<0.001) who consume alcohol were significantly associated with alcohol use. Unexpectedly, good parental monitoring (aOR, 2.46; P=0.019) and discussing serious problems with parents (aOR, 3.86; P=0.001) were significantly associated with alcohol use. Conclusion: Conclusively, policies on alcohol-related harm reduction and prevention should be developed, especially school-based programs, programs addressing family functioning, and parent-child communication, among others, should be further looked into. Future research on the school environment, adolescents’ drinking motives, and the development of practical adolescent-friendly alcohol screening tools are recommendations for improvements.